Do geographical variations in climate influence life satisfaction? - Thomas Murray; David Maddison; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2011)
Accounting for socioeconomic and demographic variables as well as country specific effects, households' willingness to pay for changes in climate is revealed using European data on reported life satisfaction. Individuals located in areas with lower average levels of sunshine and higher average levels of relative humidity are less satisfied as are individuals in locations subject to significant seasonal variation in monthly mean temperatures and rain days. Ranking regions according to the preferred climates households appear strongly to favour the Mediterranean climate over the climate of Northern Europe.
Keywords: C21; I31; Q51; Q54; 330; Life Satisfaction; Europe; Willingness to Pay; Climate; Climate Change; Klima; Zufriedenheit; Willingness to pay; Klimaveränderung; Europa